Company’s Pride Storytelling (Fantasy Theme Analysis of Psychology Approach Study to Community Communication of Pt Telkom Indonesia Retiree) - Christin, Maylanny; Suganda, Dadang; Suryana, Asep; Ratna Suminar, Jenny (International Journal of Engineering and Technology, 2018)
There are several factors influencing neglect dwindling loyalty such as the commitment of the company towards its employees, and the impact on employee loyalty. This research focused on aspects which influenced the pride of being the employees of PT Telkom so that the employee work optimally, concentrate, expressed thoughts, ideas, spent effort and time in accordance with the company objectives expected to end his tenure. This research used Ernest1 Fantasy Theme Analysis method through storytelling among PT Telkom Indonesia's retiree community. This research emphasized the main rule of communication become the primary medium in the internalization of the values that make the retirees proud of their company. The data collection was engineered by: Focus Group Discussion (FGD) and Focus Group Interviews (FGI). The purposes of this researched were to investigate: (1) what makes employees feel proud of their organization. (2) what sort of communication activities that organization do so that the employees become loyal. The results of this research showed that pride at organization located on two aspects: there was (a) Employees pride towards the company: (1) Feeling proud because the company has standard in recruiting employees. (2) Feeling proud because they were awarded in the form of pension funds. (3) Feeling proud of because the company has a clean governance and transparent (4) Feeling proud because company has contributed towards the development of Indonesia. (b) the communication activities conducted by the company: the unification of diversity of background activities employees performed with the events 'Bintal’ (Mental instilling Program) the more similar socio-cultural background of each individual then their communication will be more effective. (2) the naming of building in University Telkom by using the name of the most outer islands that have been explored by retired member of Telkom. (3) Give special time for employees retired to give the story its experience and advice for the aspiring leader at Telkom. This research contributes to the development of the science of social psychology and communication studies that strengthened the connection between pride in the company with loyalty at the company. Originality in this study lies in the use of methods Fantasy The (Fantasy Theme Analysis, Symbolic Cue, Fantasy Type, Saga) with the technique of storytelling by employees retired member of Telkom Indonesia.